Coping strategies and vulnerability to climate change of households in Mozambique - Karanja Ng'ang'a, Stanley; Maute, F.R.; Notenbaert, An Maria Omer; Herrero, Mario; Moyo, Siboniso (2012)
The purpose of this transdisciplinary project was to cogenerate methods, information and solutions between local communities, local and international scientists and policy makers involved in climate change and adaptation programmes, for coping mechanisms and adapting strategies to climate change and variability in Africa. Herewith the overall goal is to increase the adaptive capacity of agropastoralists, who are among the most vulnerable groups in Africa to climate change and variability. At a household level, a number of factors influence the nature and degree of people’s vulnerability to climate change. We conducted household-level surveys in the agropastoral areas of Mozambique. Based on this, we developed a vulnerability index at the household level and validated the value of a variety of indicators often used in vulnerability assessments. This study gives us more certainty about some variables’ influence on coping capacity; some of which are widely applicable. Income diversification, increasing access to infrastructure and saving, for example, are widely applicable and promoted adaptation options.